KAJIAN LITERATUR TENTANG INTEGRASI ARTIFICIAL INTELLIGENCE DALAM BISNIS DIGITAL BERBASIS SYARIAH - Trisena, Puja; Fauzi, Musthofa Mahfud; Rindyana, Wulan (Taksasila Edukasi Insani, 2025)
The advancement of digital technology, particularly Artificial Intelligence (AI), has driven significant transformation across various business sectors, including Sharia-based digital businesses. This study aims to comprehensively examine the potential, challenges, and opportunities of integrating AI into Sharia-compliant digital business using a qualitative, literature-based approach. The findings indicate that AI contributes significantly to enhancing operational efficiency, maintaining adherence to Sharia principles, and strengthening financial inclusion and economic distribution among the Muslim community. The application of AI has proven effective in detecting non-Sharia elements, supporting the management of halal finance, and accelerating services based on Islamic ethics. However, ethical and normative challenges must still be addressed, especially concerning algorithmic fairness, personal data protection, and the limitations of AI in understanding the complexity of Islamic jurisprudence (fiqh). Therefore, collaboration among technology experts, business practitioners, and Islamic scholars is essential to ensure that the use of AI aligns with the objectives of Sharia (maqashid syariah). This study offers a conceptual contribution to the development of ethical, inclusive, and sustainable Sharia digital business models in the technological era. Keywords : Artificial Intelligence, Sharia Digital Business, Islamic Economics, Technology Ethics, Maqashid Sharia